Scientific knowledge in brazilian and spanish national innovation systems - da Silva, Elaine [UNESP]; Valentim, Marta Lígia Pomim [UNESP]; González, Marta de La Mano (My University, 2020)
The collaborative nature of national innovation systems implies the implementation of public policies for innovation, intended to guide the action and interaction of the agents involved in the system. Universities play a relevant role in that context, being as they are major producers of scientific knowledge in countries. The general purpose of the study was to analyze national and institutional public policies and innovation indicators from Brazil and Spain related to the production and exchange of scientific knowledge. A qualitative study was conducted consisting in bibliographic and document analysis and a comparison between ST&I indicators and policies in place in Brazil and Spain. The documents analyzed were found to address interaction concepts and principles, but it is necessary to include aspects contributing to the effectiveness of integrated action and exchange of knowledge between the agents involved in the national innovation systems.
El conocimiento científico en el contexto de los sistemas nacionales de innovación de brasil y España
Keywords: Innovation generation; Innovation indicators; Innovation management; Knowledge production; National innovation systems; Public innovation policies; Scientific knowledge